2016
DOI: 10.1016/j.ajme.2015.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility pattern of genital Mycoplasmas among a group of pregnant women

Abstract: Mycoplasma hominis (MH) and Ureaplasma urealyticum (UU) are important members of genital Mycoplasmas. They are implicated in urogenital infections and complicated pregnancy (chorioamnionitis, preterm delivery, abortion, and preterm birth) as well as bacterial vaginosis and cervicitis. The administration of antimicrobial agents to pregnant women with preterm rupture of the membranes (PROM) may extend the gestation period and decrease the risks of associated complications and neonatal infections. Despite empiric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Clarithromycin is another macrolide with good antibacterial activity against Ureaplasma spp. isolated from pregnant women who showed high susceptability (82.9–86.0%) to clarithromycin . A report showed that 3.7% of pregnant patients with U. parvum colonization who were not treated with antibiotics, such as clarithromycin, had preterm birth at less than 34 weeks of gestation and late abortion.…”
Section: Therapeutic Options For Genital Ureaplasma Infection In Pregmentioning
confidence: 99%
See 1 more Smart Citation
“…Clarithromycin is another macrolide with good antibacterial activity against Ureaplasma spp. isolated from pregnant women who showed high susceptability (82.9–86.0%) to clarithromycin . A report showed that 3.7% of pregnant patients with U. parvum colonization who were not treated with antibiotics, such as clarithromycin, had preterm birth at less than 34 weeks of gestation and late abortion.…”
Section: Therapeutic Options For Genital Ureaplasma Infection In Pregmentioning
confidence: 99%
“…Among the macrolides, clarithromycin has the optimal placental passage if administered after the first trimester of pregnancy, making it a potential treatment option for genital ureaplasma infections during pregnancy . Based on antibiotic resistance studies, U. urealyticum isolated from pregnant women showed low resistance (0.9–25%) against clarithromycin …”
Section: Therapeutic Options For Genital Ureaplasma Infection In Pregmentioning
confidence: 99%
“…The current results seem to be concordant with other studies reporting the infection rate of mycoplasmas in the genital tract of pregnant women. In a previous study carried out in our country Egypt, U. urealyticum infection was detected in 21 vaginal swabs (42%) of 50 obtained from pregnant women, whereas M. hominis was detected in 14% (7/50) 26 . In addition, in the study of Bayraktar et al, 27 infection rates of vaginitis among symptomatic pregnant women were 44% (22/50) by U. urealyticum , 4% (2/50) by M. hominis , and 6% (3/50) by both organisms.…”
Section: Discussionmentioning
confidence: 79%
“…In a previous study carried out in our country Egypt, U. urealyticum infection was detected in 21 vaginal swabs (42%) of 50 obtained from pregnant women, whereas M. hominis was detected in 14% (7/50). 26 In addition, in the study of Bayraktar et al, 27 infection rates of vaginitis among symptomatic pregnant women were 44% (22/50) by U. urealyticum, 4% (2/50) by M. hominis, and 6% (3/50) by both organisms. This emphasizes that pregnancy is a risk factor for developing infection rather than just colonization.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation